The Determinants of Firm Value: A Panel Data Approach on the S&P 500 Companies - Alexandra Ioana Vintilă (Scientific Annals of Economics and Business)
Over the last two decades, the US companies have faced a series of challenges caused by the two of the most significant events, namely the global financial crisis and the Covid-19 pandemic crisis. To analyze the influence of these crises along with other factors on the firm value represented by Tobin’s Q, there were estimated unbalanced panel data multiple regression models, with cross-section fixed effects, with cross-section and period fixed effects, with cross-section random effects, and with cross-section random effects with period fixed effects, using a sample of 442 non-financial companies included in the Standard & Poor’s 500 index, over a period of 20 years, from 2004 to 2023. The independent variables are divided into three categories, namely financial indicators, corporate governance variables, and dummy variables that indicate the crisis periods. The results showed that the financial leverage, asset tangibility, liquidity, firm size, the number of meetings attended by the board members annually, the proportion of the independent members on the board and the Covid-19 pandemic crisis had a positive effect on the company value, while the firm age, CEO duality, the number of the members on the board, the proportion of the females on the board and the global financial crisis exerted a negative impact on the firm value. To better differentiate the determinants of the firm value in the context of the two major events that occurred during the analyzed period, there were estimated other empirical models using interaction variables between each dummy variable showing the crisis and the other factorial variables.